2009
DOI: 10.1021/es902165y
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Anode-Respiring Bacteria Based on Anode Potential: Phylogenetic, Electrochemical, and Microscopic Characterization

Abstract: Anode-respiring bacteria (ARB) are able to transfer electrons contained in organic substrates to a solid electrode. The selection of ARB should depend on the anode potential, which determines the amount of energy available for bacterial growth and maintenance. In our study, we investigated how anode potential affected the microbial diversity of the biofilm community. We used a microbial electrolysis cell (MEC) containing four graphite electrodes, each at a different anode potential (E(anode) = -0.15, -0.09, +0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

45
294
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 456 publications
(343 citation statements)
references
References 41 publications
45
294
1
3
Order By: Relevance
“…It is hypothesised that higher anode potentials provide the bacteria with more energy and therefore lead to a greater diversity, while low potentials allow only the most capable electrogen, i.e. Geobacter [28], to colonise the anode. This would, somewhat counterintuitively, result in lower diversity where there is higher current densities at low electrode potentials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesised that higher anode potentials provide the bacteria with more energy and therefore lead to a greater diversity, while low potentials allow only the most capable electrogen, i.e. Geobacter [28], to colonise the anode. This would, somewhat counterintuitively, result in lower diversity where there is higher current densities at low electrode potentials.…”
Section: Introductionmentioning
confidence: 99%
“…This would, somewhat counterintuitively, result in lower diversity where there is higher current densities at low electrode potentials. Using 16S rDNA clone library construction and sequencing Torres et al, [28] have observed higher diversity when higher anode potentials were imposed. Conversely Zhu et al [29] have observed that diversity was not related to imposed anode potentials when measured using 454 pyrosequencing.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed that different EETactive communities were established with various carbon substrates and different electrode potentials, and both parameters clearly affected the final community composition (Torres et al, 2009;White et al, 2009;Freguia et al, 2010;Kiely et al, 2011). However, it is poorly understood how the substrates and electrode potentials affect the developmental processes of EET-active microbial communities, and how metabolic networks are established and maintained within the community.…”
Section: Introductionmentioning
confidence: 99%
“…This IR drop may not only introduce errors in the measurements electrochemically, but also can result in biological changes in the bioanodes. When anodes in MFCs were acclimated to different set anode potentials they showed differences in startup time, power production, and electrochemical performance (Sun et al, 2012;Torres et al, 2009;Wang et al, 2009;Zhang et al, 2013;Zhu et al, 2013), likely due to the selection of different bacteria species with different anode potentials during the acclimation. Even with pure cultures the set potential can alter expression of different electron transport systems, thus affecting the actual reactions (Dumas et al, 2008;Wei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%